2016
DOI: 10.1186/s12877-016-0192-7
|View full text |Cite
|
Sign up to set email alerts
|

The association of serum procalcitonin and high-sensitivity C-reactive protein with pneumonia in elderly multimorbid patients with respiratory symptoms: retrospective cohort study

Abstract: BackgroundSerum procalcitonin and high-sensitivity C-reactive protein (hs-CRP) elevations have been associated with pneumonia in adults. Our aim was to establish their diagnostic usefulness in a cohort of hospitalized multimorbid patients ≥65 years old admitted to hospital with acute respiratory symptoms.MethodsWith a retrospective cohort study design, all multimorbid patients ≥65 years-old with acute respiratory symptoms admitted to an internal medicine hospital ward in Italy from January to August 2013 were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 30 publications
(37 reference statements)
1
44
0
3
Order By: Relevance
“…However, Steichen O et al demonstrated that the clinical usefulness of PCT to diagnose invasive bacterial infections in elderly patients appears to be very limited [ 20 ]. Nouvenne A et al noted that, for elderly patients, hs-CRP is more useful than PCT in diagnosing pneumonia [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, Steichen O et al demonstrated that the clinical usefulness of PCT to diagnose invasive bacterial infections in elderly patients appears to be very limited [ 20 ]. Nouvenne A et al noted that, for elderly patients, hs-CRP is more useful than PCT in diagnosing pneumonia [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…In several studies of elderly patients, computed tomography (CT) scan detected pneumonia in up to 47% of cases that were not identified by using chest radiographs. 89,90 There are also interobserver discrepancies in the interpretation of chest radiographs, which may be particularly problematic when portable chest radiographs are used. 91 Among residents of LTCFs, imaging has an important role in the diagnosis of pneumonia, as well as in identifying other high-risk conditions that warrant the transfer to an acute care facility.…”
Section: Imagingmentioning
confidence: 99%
“…In the same study, PCT levels were not significantly associated with pneumonia. 90 The use of CRP and PCT was evaluated for severity of pneumonia in elderly patients, and was not found to predict mortality. 101,102 Low serum albumin levels are associated with poor prognosis in CAP patients.…”
Section: Laboratory Evaluationmentioning
confidence: 99%
“…The latter is different from the cut-off-value in the general practice population (i.e. 100 mg/L), and was based on a NH study that showed adequate discriminatory power for distinguishing pneumonia with this CRP-value [33].…”
Section: Medical Training Sessionmentioning
confidence: 99%
“…CRP increases within four to 6 hours after the onset of an inflammatory reaction as well as rapidly decreases after its resolution (4 to 7 hours halftime, and 19 hours half-life) [30][31][32]. CRP POCT alongside the clinical signs and symptoms may provide the physician with valuable information for the treatment decision [33]. Studies in the general practice population showed CRP to be the strongest predictor of pneumonia, and that the reliability of the diagnosis improves when CRP is added to the evaluation of clinical signs and symptoms [19,34].…”
Section: Introductionmentioning
confidence: 99%